Extremely rapid grain growth in scallop-type Cu6Sn5 during solid–liquid interdiffusion reactions in micro-bump solder joints. (1st April 2020) - Gusak, A.M.; Tu, K.N.; Chen, Chih
Abstract: In 3D IC technology, when the size of the micro-bump solder joint is reduced to 10 µm, the scallop-type Cu6 Sn5 grains on opposite sides of the joint can interact directly by contacting each other during the solid–liquid interdiffusion reaction. Upon contact, an extremely rapid grain growth of the scallops occurs. We propose that the liquid solder wets the grain boundary between scallops and provides an extremely fast kinetic path of liquid channel for grain growth. The width of the liquid channel has been estimated to be about 1.5 nm. This is a unique phenomenon observed in micro-bump solid joints. Graphical abstract: The intermetallic compound (IMC) of Cu6 Sn5 on the opposite sides of the joint can interact directly by touching each other during the solid–liquid interdiffusion (SLID) reaction, as shown in Fig. (a) and (b). Upon touching, an extremely rapid grain growth of the IMC occurs, as seen in Fig. (c). We propose that the liquid solder wets the grain boundary of IMC and provides an extremely fast kinetic path of liquid channel for grain growth, as illustrated in Fig. (d). It is a unique phenomenon in solid joint technology when the joint becomes small. Image, graphical abstract